2020
DOI: 10.3390/ijms21238900
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Focus on Quadruplex Structures as Potential Therapeutic Targets in Cancer

Abstract: Non-canonical, four-stranded nucleic acids secondary structures are present within regulatory regions in the human genome and transcriptome. To date, these quadruplex structures include both DNA and RNA G-quadruplexes, formed in guanine-rich sequences, and i-Motifs, found in cytosine-rich sequences, as their counterparts. Quadruplexes have been extensively associated with cancer, playing an important role in telomere maintenance and control of genetic expression of several oncogenes and tumor suppressors. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 180 publications
(197 reference statements)
0
23
0
Order By: Relevance
“…[1] Non-canonical DNAs tructures include hairpins,c ruciforms, triplexes,G-quadruplexes (G4s), and i-motifs (i-DNAs). [2][3][4][5][6][7] i-DNAw as first observed in 1993 for the hexamer sequence d(TCCCCC) under acidic conditions. [8] It consists of two intercalated parallel-stranded duplexes held together by hemi-protonated cytosine-cytosine + (C:C + )b ase pairs (Figure 1A).…”
Section: Introductionmentioning
confidence: 75%
“…[1] Non-canonical DNAs tructures include hairpins,c ruciforms, triplexes,G-quadruplexes (G4s), and i-motifs (i-DNAs). [2][3][4][5][6][7] i-DNAw as first observed in 1993 for the hexamer sequence d(TCCCCC) under acidic conditions. [8] It consists of two intercalated parallel-stranded duplexes held together by hemi-protonated cytosine-cytosine + (C:C + )b ase pairs (Figure 1A).…”
Section: Introductionmentioning
confidence: 75%
“…Although G4 structures could appear as elusive entities and their biological role still requires to be elucidated in depth, the evidence that these structures (i) are stable and detectable in human genomic DNA [ 24 ]; (ii) can be detected in living cells by specific antibodies or fluorescent probes [ 25 ]; (iii) are prevalent in tumor than in normal tissues [ 26 , 27 ], alongside the evidence that some human genetic disorders are driven by defects in the unwinding activity of G4-associated enzymes [ 28 ], indicates that G4 may represent suitable druggable targets. Indeed, during the past two decades several efforts have been made in the search of small molecules able to recognize and bind to G4 structures [ 2 , 15 , 18 , 29 ]. These compounds broadly share defined structural features, including (1) a large aromatic core for π-π stacking interactions with the G-quartet; (2) one or more flexible side-chains on the aromatic core that allow introducing specific functional groups to favor the interaction with grooves, loops or individual bases of the G4 [ 30 , 31 , 32 ].…”
Section: Targeting G-quadruplex Structures In Cancermentioning
confidence: 99%
“…It has been also reported that compounds with reduced planarity (i.e., lacking the flat aromatic core) may be amenable of G4 targeting through the interaction with the grooves and/or the nucleic acid backbone [ 33 ]. To date, several small molecules belonging to distinct chemical families have been designed and characterized as G4 ligands [ 34 ] and a subset of them have been evaluated for their therapeutic potential in cancer [ 14 , 15 , 16 , 17 , 18 , 29 ].…”
Section: Targeting G-quadruplex Structures In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, contemporary research has demonstrated the importance of G4s in various cellular processes, including interactions with TFs [ 60 , 61 , 62 , 63 ]. Moreover, the targeting of the unique structure of G4s is proposed as a good tool for various diseases therapies including cancer [ 64 , 65 , 66 , 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%